Que História é essa? : percursos da História ensinada a crianças em escolas do ensino fundamental - Luiz, Miriã Lúcia (2010)
This study investigates how history is taught in early grades of elementary school. It departs from the propositions by Marc Bloch (2001) and Le Goff (2001, 2003, 2005, 2009), which allow broadening the notion of historical time, as well as the concept of historical sources. By understanding teachers as those who mediate the processes of learning and teaching history, I see them as intellectual agents of change (GIROUX, 1997) in constant formative process, always marked by reflection on their own practices (NÓVOA, 1995). I thus understand that teachers appropriate (CHARTIER, 1990) the curriculum presented to them through different ways. The curriculum therefore is not neutral (SACRISTÁN, 1998). Thus, teachers are inevitably mediators to whom I also assign the role of adaptors or, in a broader sense, creators (SACRISTÁN (1998). The curriculum, in this sense, can be understood as suggested by Ferraço (2004), i.e. in the knowledge-actions and discourse-practice networks. By means of questionnaires, observation, interviews and content analysis approach (BARDIN, 2007), I investigated the teachers‟ practice in the city of Mantenópolis in order to understand how history teaching takes place, and the appropriation these teachers make of the curriculum guidelines. In the study context, the following themes are pointed out to be taught during the classes: local history; the child‟s history; commemorative dates and temporality, for which the main resource was the coursebook. I understand that it is by these means that teachers appropriate the curricular guideline contents. I see that these are multifaceted situations, taking place in moments in which history is revealed fragmented and randomly through the predominant use of a coursebook, which shows history as distant experiences of the teachers and students'. However, in other situations, History is portrayed with its joys and pleasures, in an integrated way, blending with the other knowledge that makes up the context of early school grades. Therefore, I notice that, in the study context, History emerges as an auxiliary subject that, when integrated with other types of knowledge, contributes to students‟ learning process, especially reading and writing – essential goals at early stages